2019
DOI: 10.1111/and.13326
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress before and after surgery in benign prostatic hyperplasia patients

Abstract: The aim was to assess oxidative stress in benign prostatic hyperplasia patients and also to evaluate the effect of operation in late (60 days) post‐operative period. This study was conducted with 16 patients with benign prostatic hyperplasia and 16 healthy subjects. Serum malondialdehyde, blood 8‐hydroxy‐2′‐deoxyguanosine/deoxyguanosine, erythrocyte superoxide dismutase, serum total coenzyme Q10 and coenzyme Q10 levels were measured. Independent samples t test was used to analyse the differences between contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The oxidative stress in BPH patients has been assessed for evaluating the effects of the operation. The results suggested that the oxidative stress can be better reflected by blood level of 8-hydroxy-2'-deoxyguanosine/deoxyguanosine level compared to that of the malondialdehyde, and surgical operation attenuated the oxidative stress in the late postoperative period in BPH patients [21]. The combination of GC-MS based metabolomics and machine learning revealed that three metabolites could be promising indicators for distinguishing prostate cancer from BPH, which were L-serine, myo-inositol, and decanoic acid [22].…”
Section: Discussionmentioning
confidence: 98%
“…The oxidative stress in BPH patients has been assessed for evaluating the effects of the operation. The results suggested that the oxidative stress can be better reflected by blood level of 8-hydroxy-2'-deoxyguanosine/deoxyguanosine level compared to that of the malondialdehyde, and surgical operation attenuated the oxidative stress in the late postoperative period in BPH patients [21]. The combination of GC-MS based metabolomics and machine learning revealed that three metabolites could be promising indicators for distinguishing prostate cancer from BPH, which were L-serine, myo-inositol, and decanoic acid [22].…”
Section: Discussionmentioning
confidence: 98%
“…This was to help them improve urinary continence ability, to promote local blood circulation, accelerate the damage of nerve repair which can help patients recover automatic micturition function as soon as possible, and accelerate the removal of catheters. The removal of the urethra is more conducive to the early cessation of the patient's rehabilitation, which can promote the faster recovery of intestinal function[ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process possibly contributes to hyperplasia as well. In real-world practice, chronic inflammation was associated with worse symptoms [ 7 ], and OS was significantly decreased 60 days after prostatectomy to BPH [ 8 ].…”
Section: Introductionmentioning
confidence: 99%